Independent association between prostate-specific antigen nadir and PSA progression-free survival in first-line abiraterone acetate treatment in castration-resistant prostate cancer patients: a pilot study - Du, Hong; Xie, Wenjuan; Chen, Wenqiang; Wang, Yu; Liao, Yong; Qiu, Mingxing; Li, Jun (Frontiers in Oncology, 2024)
BACKGROUND: There is limited evidence regarding the correlation between prostate-specific antigen (PSA) kinetics and clinical outcomes. Therefore, after regulating other covariates, we studied patients with castration-resistant prostate cancer who received abiraterone acetate as the first-line treatment. Whether time to prostate-specific antigen (PSA) nadir was independently associated with PSA progression-free survival (PFS) was investigated in this study. METHODS: As a retrospective cohort study, this study totally contained 77 castration-resistant prostate cancer patients received abiraterone acetate from 2015-10 to 2021-4 in a Chinese hospital. The dependent variable was PSA-pfs and the objective independent variable was time to PSA nadir (TTPN) and Covariates involved in this study included age, duration of using ADT treatment, PSA level at baseline, time of 50% PSA decline, time of PSA decline to NadirGleason score, bone-Metastatic, previously treatment, PSA decline<50% in 3 months，PSA to Nadir in 3 months，PSA decline<90%months，PSA decline<0.2ng/ml,PSA-Flare. RESULTS: For the 77 subjects, their mean age was 72.70±8.08 years. Fully calibrated linear regression findings indicated prostate-specific antigen (PSA) decline and kinetics was positively associated with PFS (month) after adjusting confounders (β=0.77, 95% CI:0.11-1.44). Non-linear relationship was not detected between PSA decline or PSA kinetics and progression free survival. CONCLUSION: According to the data of this study, there was a correlation between early PSA changes and patients treated with abiraterone acetate.